2020
DOI: 10.1101/gr.268292.120
|View full text |Cite
|
Sign up to set email alerts
|

Pan-cancer multi-omics analysis and orthogonal experimental assessment of epigenetic driver genes

Abstract: Service Email Alerting click here. top right corner of the article or Receive free email alerts when new articles cite this article-sign up in the box at the http://genome.cshlp.org/subscriptions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…Since KATs can also acetylate non-histone proteins, it will be important to dissect out the mechanisms by which KAT8 regulates TNBC cell fitness to be able to precisely target this complex in breast cancer. Interestingly, previously published epigenome-wide libraries did not include KANSL2, KANSL3 and SS18L2 targeting sgRNAs, and therefore failed to identify strong effects of these genes on cell survival [44][45][46]. Therefore, the broad targeted gene list of EPIKOL ensures identification of true-positive hits.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since KATs can also acetylate non-histone proteins, it will be important to dissect out the mechanisms by which KAT8 regulates TNBC cell fitness to be able to precisely target this complex in breast cancer. Interestingly, previously published epigenome-wide libraries did not include KANSL2, KANSL3 and SS18L2 targeting sgRNAs, and therefore failed to identify strong effects of these genes on cell survival [44][45][46]. Therefore, the broad targeted gene list of EPIKOL ensures identification of true-positive hits.…”
Section: Discussionmentioning
confidence: 99%
“…Successful validation of individual candidate genes through follow-up competition and cell growth assays showed that EPIKOL is suitable to functionally interrogate a wide range of epigenetic modifiers. In contrast to most currently available epigenome-focused libraries, which only target chromatin modifiers such as writers, readers and erasers [44][45][46], EPIKOL targets a wider range of genes coding for chromatin complex cofactors and structural components [48]. Thus, its use will likely lead to a broader understanding of the functions of these complexes as a whole.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the enhancement of omics approaches and strategies for multi-omics data integration over the last years, we believe that this needs to be changed in the future. Thereby, not only the integration of transcriptome, proteome, and metabolome but also of further omics layers, e.g., epigenome [ 176 ], methylome [ 177 ], acetylome [ 178 ], and phosphoproteome [ 179 ], should be considered. Post-translational modifications (PTMs) are highly relevant since they regulate protein function, activity and thus, cell signaling [ 180 ].…”
Section: Discussionmentioning
confidence: 99%